2022
DOI: 10.3390/ma15197007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on Properties of Cold-Sprayed Zn–Al Composite Coatings

Abstract: Al–Zn composite coating can provide effective cathodic protection for E235 steel. This study aims to obtain the Al–Zn composite coating with the best anti-corrosion performance by optimizing the spraying temperature, spraying distance and powder-feeding motor speed. The Al and Zn powders were analyzed by scanning electron microscope (SEM), and the microstructure of the coatings prepared by different process parameters was observed by optical microscope. The mechanical and anticorrosive properties of the coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The top layer of the coating has significantly corroded. Wang et al reported similar results [34]. Simultaneously, it would appear that the corrosion products are distributed in the coating.…”
Section: Microstructure Of the Zn-al Coatingmentioning
confidence: 71%
“…The top layer of the coating has significantly corroded. Wang et al reported similar results [34]. Simultaneously, it would appear that the corrosion products are distributed in the coating.…”
Section: Microstructure Of the Zn-al Coatingmentioning
confidence: 71%
“…Unfortunately, this method is not practically applicable to steel due to the feature of the PEO process and the particulars of iron oxides. In this regard, another promising method proposed for applying a protective coating to steel is the cold spray (CS) [58][59][60].…”
Section: Introductionmentioning
confidence: 99%